Id, Ego, and Superego in This Earth of MankindNovel: A psychoanalytic feminist content analysis - Nugroho, Arif; Wulandari, Fitriya Dessi; Nety; Rifai, Dian Muhammad (Salasika, 2025)
The systematic analysis scrutinizes the psychoanalytic feminist of Nyai Ontosoroh character (a gundik- a woman who lives in a non-legal marriage with a man) as portrayed in This Earth of Mankindnovel by an Indonesian famous and influential literary figure, Pramoedya Ananta Toer. Drawing on inferential content analysis, this research depicted the psychological conflicts in the form of id, ego, and superego experienced by Nyai Ontosoroh. It was revealed that Nyai Ontosoroh's primary desires (id) centered on achieving personal freedom and independence and regaining custody of her daughter. However, she had undergone resistance from the Colonialism law (superego), which deemed her ineligible for custody and any inheritance from her former husband due to her status as a "gundik", not legally married to him. To reach a compromise, Nyai Ontosoroh took conscious and strategic steps (ego) to fight for her rights, such as marrying her daughter to a man she loved, attaining financial independence, and fighting against colonialism laws to regain custody of her daughter. This study's findings provide valuable insights for feminist activists looking to promote gender equality, as demonstrated through the character of Nyai Ontosoroh.